The purpose driven life : what on earth am I here for? - Warren, Richard, 1954- 4 0 16; 5 (Grand Rapids, Michigan : Zondervan, 2002)
Draws from the Bible to explain to Christians how to understand God's purpose for them and fulfill it in a Christlike fashion.
Includes bibliographical references.
Publisher's Weekly
Adult;Adult.
Keywords: 2 -- 0; 6; Christian life.;Christian life; 20; 2